A study on disabled people perceptions on service quality provided by The Industrial Training Center And Rehabilitation (PLPP) / Salmah Salman...[et al.] - Salman, Salmah; Mohd Nazir, Siti Nazira; Md Yusuf, Siti Nur Raidah; Ahmad, Jasmine (2010)
Service is an act or performance and an activity or a series of activities which take place in interactions with a contact person or a physical machine and which provides customer satisfaction. This study identifies the disabled people (students in PLPP) perceptions on the service quality provided by the Rehabilitation and Industrial Training Centre (PLPP) in Bangi, Selangor. Disabled person or generally referred to as ‘disabled’ are those with a physical or mental impairment that substantially limits one or more major life activities. This study focuses on the level of awareness towards the type of services provided to the disabled students such as educational and training programmes, facilities as well as services. In addition, the study identifies the satisfaction level on services provided by PLPP through self-administered questionnaire. The findings of this study contribute to the understanding of crucial factors in rendering services for the disabled students.